2022
DOI: 10.3390/ijerph192215098
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Interpretive Packaged Food Labels on Consumer Purchase Intention: The Comparative Analysis of Efficacy and Inefficiency of Food Labels

Abstract: The objectives of this study are twofold. Firstly, the current study elucidates the impact and efficacy of food labels in developing consumers’ attitudes and intentions towards the selection of nutritional food. Secondly, the inefficacy of labels in developing consumers’ attitudes and intentions towards healthy packaged food selection is demonstrated. The supportive theories of the current model are those of reasoned action and protection motivation. The data of 797 respondents have been collected from four ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 95 publications
1
10
0
Order By: Relevance
“…Structural equation modeling (SEM), which provides a quantitative test for a theoretical model and may explain both latent and observable correlations across variables (Zafar et al, 2022), is being used by the researchers around the globe (Zafar et al, 2022); therefore, we have used this technique to assess the suggested framework and hypotheses. SEM also explains a group of connected hypotheses by calculating the relationships between numerous independent and dependent variables in a structural model (Gefen et al, 2000; Zafar et al, 2022). Sufficient goodness-of-fit has been found in the SEM’s overall model fit: X 2 /df = 3.26, RMSEA = 0.058, CFI = 0.84, GFI = 0.79, and adjusted GFI = 0.75, NFI = 0.78.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural equation modeling (SEM), which provides a quantitative test for a theoretical model and may explain both latent and observable correlations across variables (Zafar et al, 2022), is being used by the researchers around the globe (Zafar et al, 2022); therefore, we have used this technique to assess the suggested framework and hypotheses. SEM also explains a group of connected hypotheses by calculating the relationships between numerous independent and dependent variables in a structural model (Gefen et al, 2000; Zafar et al, 2022). Sufficient goodness-of-fit has been found in the SEM’s overall model fit: X 2 /df = 3.26, RMSEA = 0.058, CFI = 0.84, GFI = 0.79, and adjusted GFI = 0.75, NFI = 0.78.…”
Section: Resultsmentioning
confidence: 99%
“…Using a convenience sampling technique, telemedicine service receivers of Bangladesh were invited online to participate in a survey. We used convenience sampling because it is cost-effective and makes data available (Li et al, 2022; Zafar et al, 2022). Participation was voluntary, and participants were assured that their information would be kept private.…”
Section: Methodsmentioning
confidence: 99%
“…It is critical to understand the ingredients involved in food products before purchasing. Consumers generally read the information on the product labels, especially when purchasing food products (Zafar, 2022). Muslims' positive ATT in fulfilling their religious belief encourages them to search for a halal logo before making a purchase decision (Al-Kwifi et al, 2021).…”
Section: Theory Of Planned Behavior and Halal Label Perceived Importancementioning
confidence: 99%
“…The growing number of demands worldwide has encouraged authorities in many countries to issue halal obligation policies (Zafar, 2022). Accordingly, manufacturers aim to capture the sizeable Muslim segment by presenting their "halalness," using the official halal label, even in a Muslim-minority country such as Japan (Saville and Mahbubi, 2021).…”
Section: Theory Of Planned Behavior and Halal Label Perceived Importancementioning
confidence: 99%
“…However, there has been a direct link between social well-being and the energy sector (Local Burden of Disease 2021; Moradi et al, 2021;Schmidt et al, 2022). Energy transition has become a need of time to secure the future generation from a dirty environment (Jiakui et al, 2023;Zafar et al, 2022).…”
Section: Introductionmentioning
confidence: 99%